Combinatorial immunotherapy with anti-ROR1 CAR NK cells and an IL-21 secreting oncolytic virus against neuroblastoma - Yaya Chu; Meijuan Tian; Uksha Saini; Jessica Ayala-Cuesta; Kayleigh Klose; Alyssa S. Mendelowitz; Keira Foley; Mehmet F. Ozkaynak; Wen Luo; Timothy P. Cripe; Dean A. Lee; Kevin A. Cassady; et al. (Molecular Therapy: Oncology)
Children with recurrent/metastatic neuroblastoma (NB) have a dismal survival (<25%). Novel therapies are desperately needed. Receptor tyrosine kinase-like orphan receptor 1 (ROR1) is highly expressed on NB. C021 is a selective oncolytic herpes simplex virus modified to overexpress human interleukin-21 (hIL-21), a cytokine that enhances natural killer (NK) cell cytotoxicity. In the current study, we successfully engineered ex-vivo-expanded NK cells to express a chimeric antigen receptor (CAR) against ROR1 using mRNA electroporation and investigated the efficacy of anti-ROR1-CAR-NK cells combined with C021 in targeting ROR1+ NB. We found that C021-infected NB cells secreted hIL-21 in vitro and in vivo. Compared to the non-cytokine-secreting parental virus C134, C021 significantly enhanced the in vitro cytotoxicity (p < 0.05) of anti-ROR1-CAR-NK cells with increased interferon (IFN)-γ (p < 0.05), granzyme B (p < 0.05), and perforin (p < 0.05) secretion against NB cells. Furthermore, the combination of C021 and anti-ROR1-CAR-NK cells significantly extended the survival of human NB xenografted NSG mice compared to controls (mock NK, ROR1-CAR-NK, C134, C021, C134+ROR1-CAR-NK, and C021+mock NK). Our results suggest that cytokine-secreting oncolytic virus in combination with CAR-NK cells is a novel, effective immunotherapeutic approach for high-risk NB.